2014
DOI: 10.1098/rsta.2013.0040
|View full text |Cite
|
Sign up to set email alerts
|

The ocean's role in polar climate change: asymmetric Arctic and Antarctic responses to greenhouse gas and ozone forcing

Abstract: In recent decades, the Arctic has been warming and sea ice disappearing. By contrast, the Southern Ocean around Antarctica has been (mainly) cooling and sea-ice extent growing. We argue here that interhemispheric asymmetries in the mean ocean circulation, with sinking in the northern North Atlantic and upwelling around Antarctica, strongly influence the sea-surface temperature (SST) response to anthropogenic greenhouse gas (GHG) forcing, accelerating warming in the Arctic while delaying it in the Antarctic. Fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
148
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(164 citation statements)
references
References 72 publications
5
148
2
Order By: Relevance
“…They found that the loss of ozone gave a year-round decrease in Antarctic sea ice, with the largest decrease in austral summer. By contrast, Marshall et al [34] suggested that the loss of stratospheric ozone above the Antarctic would lead to a decrease in SSTs around the continent, which would be conducive to more sea ice. While for the remainder of the twenty-first century, a modelling study by Smith et al [35] suggested that projected ozone loss will mitigate Antarctic sea ice loss.…”
Section: Mechanisms That May Be Contributing To the Observed Sea Ice mentioning
confidence: 99%
See 1 more Smart Citation
“…They found that the loss of ozone gave a year-round decrease in Antarctic sea ice, with the largest decrease in austral summer. By contrast, Marshall et al [34] suggested that the loss of stratospheric ozone above the Antarctic would lead to a decrease in SSTs around the continent, which would be conducive to more sea ice. While for the remainder of the twenty-first century, a modelling study by Smith et al [35] suggested that projected ozone loss will mitigate Antarctic sea ice loss.…”
Section: Mechanisms That May Be Contributing To the Observed Sea Ice mentioning
confidence: 99%
“…A more recent suggestion is that the responses of surface temperatures and sea ice in the Southern Ocean exhibit a two timescale response to ozone-induced increases in the polarity of the SAM [34]. The initial short timescale response is a surface cooling and increase in SIE, which is then followed by surface warming and SIE reduction as upwelling of warm water from below becomes established.…”
Section: Mechanisms That May Be Contributing To the Observed Sea Ice mentioning
confidence: 99%
“…The ratio of land warming to ocean warming is found to be greater than unity across all scenarios and models for both transient and equilibrium warming, due to differences in surface sensible and latent heat fluxes, boundary layer lapse rate and relative humidity, and cloud cover 8 . Muted warming is found in the Southern Ocean where excess surface heat is mixed into the ocean interior more effectively 9,10 . A similar feature is found in the North Atlantic subpolar gyre.…”
Section: Temperaturementioning
confidence: 99%
“…Extratropical heating anomalies in particular, even when zonally bound (Kang et al 2014), are found to be able to impact the ITCZ position globally, with the ITCZ shifting away from the cooling hemisphere (Broccoli et al 2006;Kang et al 2008Kang et al , 2009Chiang and Friedman 2012;Donohoe et al 2013;Schneider et al 2014). Evidence for a highlatitude forcing of tropical climate comes from numerous modeling and observational studies which suggest that changes in land and sea ice cover, AMOC strength and meltwater pulses all can impact the meridional position of the ITCZ (Chiang et al 2003;Chiang and Bitz 2005;Timmermann et al 2007;Deplazes et al 2013;Fučkar et al 2013;Marzin et al 2013;Marshall et al 2014;Menviel et al 2014;Deser et al 2015). Especially sea ice cover is known to be strongly rectified by precessional forcing (Tuenter et al 2005).…”
Section: •-mentioning
confidence: 99%